Nausea e vomito em laparoscopia ginecologica: Efeitos do oxido nitroso e da metoclopramida - Ganem, Eliana Marisa [UNESP] (1997)
Background and Objectives - Gynecological laparoscopy causes high postoperative morbidity, mainly due to occurrences such as nausea and vomiting. They result from a great multiplicity of etiologies and drugs used in anesthesia may function as contributing factors. Both the emetic properties of nitrous oxide and the efficacy of metoclopramide as antiemetic agent are controversial. This study was undertaken to determine the effects of both drugs, when used alone or in combination. Methods - Eighty three physical status ASA I and II women were studied. They were premedicated with midazolam before induction of anesthesia with alfentanil and propofol. Anesthesia was maintained with isoflurane with or without nitrous oxide in oxygen. Muscle relaxation was achieved with atracurium. There were 4 groups of patients: GI: midazolam, alfentanil, propofol, atracurium, isoflurane/oxygen; GII: midazolam, alfentanil, propofol, atracurium, isoflurane/nitrous oxide/oxygen; GIII: metoclopramide, midazolam, alfentanil, propofol, atracurium, isoflurane/oxygen; GIV: metoclopramide, midazolam, alfentanil, propofol, atracurium, isoflurane/nitrous oxide/oxygen. The incidence of nausea and vomiting was assessed both in the recovery room (RR) and in the ward. Results - There were no significant differences as regards age, weight and height of the patients and duration of anesthesia and surgery. Nausea and vomiting were more frequent in patients who received N2O (GII, 50%; GIV, 33%), as compared to those who didn't receive this agent (GI and GII, 9.5% and 14.35%, respectively). Metoclopramide decreased the incidence of nausea and vomiting in the recovery room, in patients who didn't receive N2O (GII). These patients remained in the recovery room for 90 minutes. Conclusions - N2O increases the incidence of nausea and vomiting and metoclopramide is effective in reducing these complications only in the recovery room.